The Role of Sports Medicine in Preventing and Managing Common Injuries in Athletes - Kattoof, Karrar Yaareb (Indonesian Journal Publisher, 2024)
Many international athletic organizations have proposed injury-reduction strategies. These practices include injury screening, emergency medical care, along with injury management measures prior to return-to-play. The extent to which these methods are being adopted in a developing nation like Iraq is uncertain. This paper was contributed to study the role of sports medicine in preventing and managing common injuries in athletes. Our paper focused on the role of sports medicine in treating injured athletes in Iraq. To build up, our methodology’s study was enrolled rate of acute injuries for 80 cases based on organized the demographic characteristics of sports players with three basics which are football, athletics, and handball. The data were analysed using the SPSS program. This study was presented a cumulative analysed and covered all 80 cases during period from 17th January 2022 to 19th March 2023.mThe findings demonstrated a lack of pre-season screening and return-to-play preparedness for all injured athletes. Furthermore, for the majority of injury categories, best practice standards were not followed. This study identified constraints, including sports resource providers' inadequate knowledge, insufficient and insufficiently specialized facilities for treating injured athletes, and policies mandating treatment for injured athletes. These obstacles hinder the implementation of best medical practices.